NATO SPECIAL TERMINOLOGY IN THE CONTEXT OF MILITARY TERMINOLOGICAL ACTIVITIES WITHIN THE LINGUISTIC SUPPORT - Lysychkina, Iryna; Lysychkina, Olha; Protcenko, Yevhenii (Honor and Law, 2022)
This article highlights the research results concerning the English-Ukrainian translation peculiarities of the NATO special terminology to denote the security and defense sector activities. This terminology is of special significance for the military terminological activity within the linguistic support as a relatively new domain of the troops’ (forces’) support due to its special value for the National Guard of Ukraine in terms of establishing and maintaining its cross-cultural communication with the NATO allies and partners. The research was based on the English-Ukrainian and Ukrainian-English glossary "NATO Glossary of Defense and Security Policy Terms", developed under the DCAF in 2017. The choice of the equivalents for special terms to denote defence and security sector activities is grounded on the principles of concepts coherence, accuracy of wording, the term etymology, and the semantic content comparative analysis of the terminological units and their equivalents in Ukrainian and English. It has been defined that the terms functional identity in both languages allows preserving the nominative and systematic nature of the term. The typical translation methods for the analyzed terminological units have been identified (lexico-semantic shifts, loan translation, and explication), as well as the structural and compositional patterns of equivalents selection in the Ukrainian language. The majority (64,5 %) of the analyzed glossary terms are used to denote the activities of the National Guard of Ukraine. The research results underline the importance of military terminological activity of the National Guard of Ukraine in order to systematize the terminological system of this agency and, in a broader context, to better understand military and law enforcement activities of similar law enforcement agencies of other countries.